Effects of Microplastics Exposure on the Acropora sp. Antioxidant, Immunization and Energy Metabolism Enzyme Activities - Xiao, Baohua; Li, Dongdong; Liao, Baolin; Zheng, Huina; Yang, Xiaodong; Xie, Yongqi; Xie, Ziqiang; Li, Chengyong (Frontiers in Microbiology, 2021)
Microplastic pollution in marine environments has increased rapidly in recent years, with negative influences on the health of marine organisms. Scleractinian coral, one of the most important species in the coral ecosystems, is highly sensitive to microplastic. However, whether microplastic causes physiological disruption of the coral, via oxidative stress, immunity, and energy metabolism, is unclear. In the present study, the physiological responses of the coral Acropora sp. were determined after exposure to polyethylene terephthalate (PET), polyamide 66 (PA66), and polyethylene (PE) microplastic for 96 h. The results showed that there were approximately 4–22 items/nubbin on the surface of the coral skeleton and 2–10 items/nubbin on the inside of the skeleton in the MPs exposure groups. The density of endosymbiont decreased (1.12 × 105–1.24 × 105 cell/cm2) in MPs exposure groups compared with the control group. Meanwhile, the chlorophyll content was reduced (0.11–0.76 μg/cm2) after MPs exposure. Further analysis revealed that the antioxidant enzymes in coral tissues were up-regulated (Total antioxidant capacity T-AOC 2.35 × 10–3–1.05 × 10–2 mmol/mg prot, Total superoxide dismutase T-SOD 3.71–28.67 U/mg prot, glutathione GSH 10.21–10.51 U/mg prot). The alkaline phosphatase (AKP) was inhibited (1.44–4.29 U/mg prot), while nitric oxide (NO) increased (0.69–2.26 μmol/g prot) for cell signal. Moreover, lactate dehydrogenase (LDH) was down-regulated in the whole experiment period (0.19–0.22 U/mg prot), and Glucose-6-phosphate dehydrogenase (G6PDH) for cell the phosphate pentoses pathway was also reduced (0.01–0.04 U/mg port). Results showed that the endosymbiont was released and chlorophyll was decreased. In addition, a disruption could occur under MPs exposure, which was related to anti-oxidant, immune, and energy metabolism.